Impact of Government Accounting Standards, Human Resource Competency, and Accounting Information Systems on the Quality of Financial Statements - Maha Dewi, Anak Agung Istri Agung; Kresnandra, Anak Agung Ngurah Agung (E-Jurnal Akuntansi; Vol 35 No 2 (2025)DO - 10.24843/EJA.2025.v35.i02.p12, 2024)
The financial reports of Badung Regency illustrate the role of financial reporting in promoting accountability and transparency within local government financial management. This study aims to evaluate the impact of government accounting standards (GAS) implementation, human resource (HR) competencies, and accounting information systems (AIS) on the quality of financial statements. A sample of 84 local government officials was purposively selected from a total population of 241. The data was analyzed using multiple linear regression with SPSS version 26. The findings reveal that while HR competency does not significantly influence the quality of financial statements, the implementation of GAS and AIS does contribute positively. These results provide valuable insights for researchers and readers regarding the influence of GAS, HR competency, and AIS adoption on the quality of financial reporting in Badung Regency. Keywords: Government Accounting Standards Implementation; Human Resource Competence; Accounting Information Systems; Financial Statements Quality.